Pengaruh Fleksibilitas Keuangan, Struktur Modal, dan Profitabilitas terhadap Return Saham - Jao, Robert; Daromes, Fransiskus Eduardus; Holly, Anthony; Sariri, Harly (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2024)
This research aims to analyze the influence of financial flexibility, capital structure, and profitability on stock returns. The main theory used to explain the relationship between variables is signaling theory. The research population consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) with an observation period of 2018–2022. Sample selection was carried out purposively. The analysis technique used is multiple linear regression analysis. This research finds that financial flexibility and profitability have a positive and significant effect on stock returns, while capital structure has a negative and significant effect on stock returns.